Recent Trends in Sarcasm Detection on Online Social Networks - Ranganath, K; Sallauddin, MD; Shabana (International Journal of Computer Sciences and Engineering, 2025)
Online Social Networks become largest platform to express people feelings, opinions, views and real time events such as live tweets etc. Example Twitter has 315 million monthly active users, eighty two percent of active users on mobile and millions of tweets are being circulated through twitter every day. Various organizations as well as companies are interested in twitter data for finding the views of various people towards their products or events. Sarcasm refers to expressing negative feelings using positive words. To detect sarcasm among those tweets is comparatively more difficult. This paper discussed various approaches to find sarcasm on twitter. With the help of sarcasm detection, companies could analyze the feelings of user about their products. This is helpful for companies, as the companies could improve their quality of product.